2020
DOI: 10.1002/jcp.29961
|View full text |Cite
|
Sign up to set email alerts
|

Lutein inhibits breast cancer cell growth by suppressing antioxidant and cell survival signals and induces apoptosis

Abstract: Reduced risk of breast cancer upon intake of lutein-rich food supplements creates an interest to investigate the molecular mechanism underlying the growth inhibitory potential of lutein in MCF-7 and MDA-MB-231 cells. Lutein purified from Spinacia oleracea was identified by high-performance liquid chromatography and liquid chromatography-mass spectrometry. The cell viability was measured by watersoluble tetrazolium-1 assay. The intracellular reactive oxygen species level was examined by 2′,7′-dichlorofluorescei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…epNPs have been reported to contain various biologically active molecules [13,14,16,17]. Lutein and zeaxanthin, the xanthophylls present in corn [28,29], are known to exhibit antitumor effects through regulation of cell cycle or cell apoptosis [42][43][44]. It has been reported that zeaxanthin induced cell cycle arrest at the G2/M phase and apoptosis through the ROS-mediated MAPK, AKT, NF-κB, and STAT3 signaling pathways [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epNPs have been reported to contain various biologically active molecules [13,14,16,17]. Lutein and zeaxanthin, the xanthophylls present in corn [28,29], are known to exhibit antitumor effects through regulation of cell cycle or cell apoptosis [42][43][44]. It has been reported that zeaxanthin induced cell cycle arrest at the G2/M phase and apoptosis through the ROS-mediated MAPK, AKT, NF-κB, and STAT3 signaling pathways [43].…”
Section: Discussionmentioning
confidence: 99%
“…Lutein and zeaxanthin, the xanthophylls present in corn [28,29], are known to exhibit antitumor effects through regulation of cell cycle or cell apoptosis [42][43][44]. It has been reported that zeaxanthin induced cell cycle arrest at the G2/M phase and apoptosis through the ROS-mediated MAPK, AKT, NF-κB, and STAT3 signaling pathways [43]. High-performance liquid chromatography analysis in the present study con rmed the presence of lutein and zeaxanthin in cNPs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of lutein against prostate, breast, and cancer cells have been reported elsewhere [96,97]. It has been shown that lutein could suppress the phosphorylation of protein kinase B, ERK 1/2, and NFkB in breast cancer cells [98]. Lutein has been shown to inhibit breast cancer cells and increase the efficacy of a chemotherapeutic [99].…”
Section: Luteinmentioning
confidence: 98%
“…In this regard, LUT inhibited cell growth and induced apoptosis in two breast cancer lines, the non-invasive MCF-7 and invasive MDA-MB-231 cells. The mechanisms underlying these effects were associated with an inhibition of the transcription factor Nrf2 and its target genes SOD-2 and HO-1, as well as a down-regulation of cell survival markers such as pAkt, pERK, and NF-κB [407]. Other mechanisms involved in the anti-breast cancer effects of this carotenoid include inhibition of glycolysis [408], suppression of cell cycle progression, stimulation of p53 signaling, and an increase in cellular heat shock protein 60 expression [409].…”
Section: In Vitro Studiesmentioning
confidence: 99%